Racial disparities in the cognition-health relationship - Owen Thompson (University of Massachusetts, Department of Economics, 2011)
This paper investigates how the association between cognitive achievement and self-rated health in middle age differs by race, and attempts to explain these differences. The role of cognition in health determination has received only limited empirical attention, and even less is known about how race may affect this relationship. Using data from the NLSY, I find that while whites with higher cognitive achievement scores tend to report substantially better general health, this relationship is far weaker or wholly absent among blacks. Further tests suggest that about 35% of this racial difference can be explained by behavioral decisions during adulthood, and that another portion of the disparity may trace back to prenatal and early childhood experiences. The paper closes by noting that its results are broadly consistent with explanations of the racial health gap that emphasize entrenched forms of racial discrimination.
Keywords: 330; Cognition; Health; Race; AFQT; Birth Weight